Model Pemasaran Inklusif Berbasis Kearifan Lokal untuk Memperkuat Kedaulatan Pangan dan Meningkatkan Ekonomi Masyarakat Pulau Pahawang - Prikurnia, Anas Khair; Kurniawan, Rudi (Jurnal Doktor Manajemen (JDM), 2025)
This study examines the development of an inclusive marketing model based on local wisdom to strengthen food sovereignty and enhance the economic resilience of communities in Pahawang Island, Lampung. The research uses mixed methods with explanatory survey design, combining qualitative and quantitative data. Primary data were collected through in-depth interviews, participatory observations, and structured surveys involving local residents, tourists, and small business actors. Quantitative analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to identify relationships among variables influencing the success of inclusive marketing strategies. The results reveal that limited market access, capital, and managerial capacity are key challenges for local enterprises. Integration of local cultural values into marketing strategies significantly improves product competitiveness and strengthens food sovereignty. The findings of this study suggest that a context-specific inclusive marketing model can effectively empower coastal communities, promote sustainable tourism, and support community-based economic development. This model offers practical insights for policymakers, tourism managers, and small businesses in designing marketing strategies that are both inclusive and locally grounded.